APPARATUS DIFFICULTY IN GROUPS ROUTINES OF ELITE RHYTHMIC GYMNASTICS AT THE PORTIMÃO 2009 WORLD CUP SERIES - Lurdes Ávila-Carvalho; Maria da Luz Palomero; Eunice Lebre (Science of Gymnastics Journal)
The aim of this study was to establish whether a pattern exists in the type of apparatus specific elements chosen by elite rhythmic gymnastics groups. Twenty six group exercise routines (5 hoops, and 3 ribbons and 2 ropes) performed by thirteen groups at the Portimão 2009 World Cup Series gymnastics competition were analysed. Results: (a) mastery and risk with throw: (i) all groups preferred using throws during a body flight; (ii) in the 3 ribbons and 2 ropes routines the use of catches during an element with rotation was most common, whilst in the 5 hoops routines catches without the help of the hands were used most frequently; (iii) compulsory rotations were the most commonly used elements in the 5 hoops routines, whereas the additional rotation was preferred in the 3 ribbons and 2 ropes routines. (b) mastery without throw: (i) rotations and handlings were the most frequently used elements in the 5 hoops routines whilst snakes & spirals were preferred in the 3 ribbons and 2 ropes routines; (ii) there were no records of risk without throw. (c) with regard to collaborations (COLL) the most frequently used were the COLL RR1 (these include a large throw with risk of loss of visual contact with the apparatus during its flight, as well as passing over, below or through one or several apparatus or other gymnasts during the flight of the apparatus) in the 5 hoops routines and the COLL with throw in the 3 ribbons and 2 ropes routines. This study demonstrates that it is possible to broadly identify and describe patterns of element use for each apparatus type for 5 hoops, and 3 ribbons and 2 ropes routines.